COMMUNICATION PATTERNS OF COUNSELING FROM PRISON OFFICERS TO COMMUNITY INMATES IN CLASS II A ADULT WOMEN'S PRISON IN TANGERANG CITY CASE STUDY OF COMMUNITY INMATES IN DRUG CASES - Afni Yoana Tjahyani Gusma; Rifky Maulana; Dwi Arini Yuliarti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The Class IIA Women's Correctional Facility in Tangerang City is the only women’s prison in the city and the largest of its kind in Indonesia, with the capacity to accommodate the highest number of female inmates. This study aims to explore the communication patterns employed by correctional officers in guiding and rehabilitating inmates, with a specific focus on those convicted of drug-related offenses. Employing a qualitative research method and an ethnographic approach, the study enables direct observation of the interactions between correctional staff and inmates. The research is grounded in DeVito’s Interpersonal Communication Theory. The subjects of this study are correctional officers at the Class IIA Women’s Correctional Facility in Tangerang City. Data were collected through literature review, documentation, observation, and interviews. The findings reveal two primary categories of communication-based rehabilitation patterns: (1) personality development and (2) skill development. Communication flows within the facility occur in three directions: upward, downward, and horizontal. The study also identifies several communication barriers, categorized as internal (infrastructure limitations, inmate behavior, attitudes, and language) and external (societal stigma).